The Crafting of the 10,000 Things : Knowledge and Technology in Seventeenth-Century China. - Schäfer, Dagmar (Alexander von Humboldt in English., 2011)
The last decades of the Ming dynasty, though plagued by chaos and destruction, saw a significant increase of publications that examined advances in knowledge and technology. Among the numerous guides and reference books that appeared during this period was a series of texts by Song Yingxing (1587-1666?), a minor local official living in southern China. His Tiangong kaiwu, the longest and most prominent of these works, documents the extraction and processing of raw materials and the manufacture of goods essential to everyday life, from yeast and wine to paper and ink to boats, carts, and firea.